105 Does Serum Cholesterol Correlate With Achilles Tendon Structure?. (5th September 2014) - Tilley, Benjamin; Cook, Jill; Docking, Sean; Gaida, Jamie
Abstract : Introduction: Up to 30% of Achilles tendinopathy presents in non-active individuals [Rolf 1997] and an association between adiposity and tendinopathy has been highlighted [Gaida 2009a]. Inactivity and adiposity are both associated with unfavourable serum lipid parameters. Individuals with Achilles tendinopathy have a dyslipidaemic profile [Gaida 2009b] and the extreme cholesterol levels seen in familial hypercholesterolaemia are associated with a 6-fold increased lifetime prevalence of Achilles tendon pain (47% versus 7%) [Beeharry, 2006]. It is unknown whether an association exists between lipid parameters and tendon structure in the general population. Methods: Serum lipids and Achilles tendon structure were measured in healthy participants. Lipid parameters included total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG). Glucose (GLU) was also measured. Ultrasound tissue characterisation (UTC) was used to quantify Achilles tendon structure; echo-types I (green) and II (blue) were used for analysis. Height, weight and waist circumference were measured. Physical activity level and history of Achilles tendon pain were recorded via questionnaire. Results: The 67 participants recruited included 42 men and 25 women (Table 1 ). The physical activity level was 113 ± 442 min/week. Sixteen participants (24%) reported a history of Achilles tendon pain. There were no statistically significant correlations between echo-types I/II and any of the lipid measures (Table 3, Figure 1 ). Discussion: This study did not show an association between cholesterol and tendon structure. While there was significant variability in the UTC measured tendon structure, the lipid results were relatively homogenous. For example, TC results were clustered between 4.0 and 6.0 mmol/L, suggesting that a vast majority of the participants are fundamentally "normal". Thus, cholesterol at this level is not correlated with altered tendon structure. References: Beeharry et al . Ann Rheum Dis, 2006;65(3):312–5 Gaida et al . Arthritis Rheum, 2009a;27;61(6):840–9 Gaida et al . Med Sci Sports Exerc, 2009b; 31;41(6):1194–7 Rolf et al . Foot Ankle Int. 1997;18(9):565–9